Association between ascending aortic diameter and coronary artery dilation: a demographic data analysis. (December 2016) - Hatemi, Ali Can; Tongut, Aybala; Özyedek, Zeki; Çerezci, İsmail; Özgöl, İlhan; Perk Gürün, Hande
Objective: Coronary artery dilations (CDs), a subgroup of coronary artery anomalies (CAAs), are relatively rare but important cardiac pathologies. They are considered to be linked to coronary atherosclerosis in most cases. Methods: The demographic data, multi-slice computed tomographic coronary angiography data, coronary calcium score, and ascending aortic diameter (AAD) of 1538 patients were reviewed. In total, 197 (12.8%) patients (166 men, 31 women; age 15 – 84 years; mean 55.78 ± 12.32 years) with CAAs were identified, and 81 (5.3%) patients (70 men, 11 women; age 27 – 80 years; mean 56.63 ± 12.06 years) had CDs. Multiple regression and correlation analyses were performed in all 1538 patients to predict the association between the AAD and the presence of CD and thus their correlation with atherosclerosis. Results: The AAD was significantly larger in patients with than without CAAs and CDs. Male sex was significantly more prevalent in patients with CAAs and CDs. According to the multiple logistic regression model, male sex increased the risk of CD by 2.650 and the risk of CAA by 2.017, while hyperlipidaemia decreased the risk of CAA by 0.681. While a moderately weak correlation between the AAD and age was observed in patients with CDs, no correlation was found between the AAD and coronary calcium score. Conclusion: Although the natural history and physiopathology of CDs is not yet fully understood, the present study shows an association between the AAD and the presence of CDs but a lack of association between atherosclerosis and CDs.